2020
DOI: 10.1186/s13045-020-01007-9
|View full text |Cite|
|
Sign up to set email alerts
|

MCL-1 inhibitors, fast-lane development of a new class of anti-cancer agents

Abstract: Cell death escape is one of the most prominent features of tumor cells and closely linked to the dysregulation of members of the Bcl-2 family of proteins. Among those, the anti-apoptotic family member myeloid cell leukemia-1 (MCL-1) acts as a master regulator of apoptosis in various human malignancies. Irrespective of its unfavorable structure profile, independent research efforts recently led to the generation of highly potent MCL-1 inhibitors that are currently evaluated in clinical trials. This offers new p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
111
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 157 publications
(190 reference statements)
2
111
0
1
Order By: Relevance
“…We also previously showed that in luminal breast cancers, MCL-1 expression in tumor cells was extrinsically favored by neighboring CAFs, which themselves exhibit high MCL-1 expression [13]. Our study thus brings support to the notion that a MCL-1 antagonist may improve the treatment of breast cancer [20,25] while putting forth an effect not only on cancer cells but also on non-malignant cells that interact with them. One implication is that the therapeutic potential of such a BH3 mimetic may be preclinically overlooked if reductive models using only tumor cells are used.…”
Section: Discussionsupporting
confidence: 83%
“…We also previously showed that in luminal breast cancers, MCL-1 expression in tumor cells was extrinsically favored by neighboring CAFs, which themselves exhibit high MCL-1 expression [13]. Our study thus brings support to the notion that a MCL-1 antagonist may improve the treatment of breast cancer [20,25] while putting forth an effect not only on cancer cells but also on non-malignant cells that interact with them. One implication is that the therapeutic potential of such a BH3 mimetic may be preclinically overlooked if reductive models using only tumor cells are used.…”
Section: Discussionsupporting
confidence: 83%
“…The most common cause of this is stabilization of Mcl-1 [140]. This, along with the fact that Mcl-1 is essential for the development and survival of AML cells, has led to the development of selective Mcl-1 inhibitors [141]. Sharon et al used CRISPR knockout screen to determine that ribosome-targeting antibiotics such as tedizolid can overcome venetoclax resistance by suppressing mitochondrial translation and respiration, and activating the cellular stress response [142].…”
Section: Mitochondrial Priming and Bcl-2 Protein Familymentioning
confidence: 99%
“…Therefore, combination of CDK9 inhibitors with those against MCL-1 could also significantly improve the effect of the CDK9 inhibitors. Several such inhibitors are undergoing clinical trials and have been reviewed elsewhere [178,179]. Other potential combinations could be with inhibitors of XIAP [180] had recently reported that inhibiting CDK9 activity with their newly developed inhibitor i-CDK9 suppressed phosphorylations of RNAP II at S2 and SPT5 at T775, induced genomewide pausing of RNAP II at gene promoters.…”
Section: Discussionmentioning
confidence: 99%